Cancer‐associated fibroblasts induce an aggressive phenotypic shift in non‐malignant breast epithelial cells via interleukin‐8 and S100A8. Issue 10 (21st March 2021) - Lim, Hyesol; Koh, Minsoo; Jin, Hao; Bae, Mijeong; Lee, Seung‐Yeon; Kim, Kyoung Mee; Jung, Joohee; Kim, Hyun Jeong; Park, So Yeon; Kim, Hoe Suk; Moon, Woo Kyung; Hwang, Sejin; et al.
Abstract: Cancer‐associated fibroblasts (CAFs) in the tumor microenvironment have been associated with tumor progression in breast cancer. Although crosstalk between breast cancer cells and CAFs has been studied, the effect of CAFs on non‐neoplastic breast epithelial cells is not fully understood to date. Here, we investigated the effect of CAFs on aggressive phenotypes in non‐neoplastic MCF10A breast epithelial cells. CAFs induced epithelial‐to‐mesenchymal transition (EMT) and invasive phenotype in MCF10A cells. S100A8, a potential prognostic marker in several cancers, was markedly increased in MCF10A cells by CAFs. S100A8 was crucial for CAFs‐induced invasive phenotype of MCF10A cells. Among cytokines increased by CAFs, interleukin (IL)‐8 induced S100A8 through transcription factors p65 NF‐κB and C/EBPβ. In a xenograft mouse model with MCF10A cells and CAFs, tumor was not developed, suggesting that coinjection with CAFs may not be sufficient for in vivo tumorigenicity of MCF10A cells. Xenograft mouse tumor models with MDA‐MB‐231 breast carcinoma cells provided an in vivo evidence for the effect of CAFs on breast cancer progression as well as a crucial role of IL‐8 in tumor growth and S100A8 expression in vivo. Using a tissue microarray of human breast cancer, we showed that S100A8 expression was correlated with poor outcomes. S100A8 expression was more frequently detected in cancer‐adjacent normal human breast tissues than in normal breast tissues. Together, this study elucidated a novel mechanism for the acquisition of invasive phenotype of non‐neoplastic breast cells induced by CAFs, suggesting that targeting IL‐8 and S100A8 may be an effective strategy against breast cancer. Abstract : Our study demonstrated that cancer‐associated fibroblasts (CAFs) in tumor microenvironment induced phenotypic transformation of non‐neoplastic human breast epithelial cells into invasive phenotype, in which IL‐8 and S100A8 played crucial roles. We elucidated a molecular mechanism underlying the acquisition of aggressive phenotype of non‐neoplastic cells by CAFs, providing information on the prevention or treatment of recurrent breast cancer.